Phytochemical Components, Antioxidant, Antibacterial, and Synergistic Effects of Endemic Sideritis trojana Extract in Combination with Antibiotics on Human Pathogens - Mehzat Altun (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In recent years, dramatically rising multidrug-resistant bacteria (MDR) and side effects of antibiotics lead ethnopharmacology to discover novel antimicrobials derived from plants for bacterial infections. Traditionally, decoction or infusion of the species of Sideritis has been used for the treatment of diseases such as cough, stomach, gastrointestinal, and kidney disorders. In this study, we aimed to investigate the antioxidant and antibacterial activity of the ethanolic extract of Sideritis trojana (S.trojana) and its synergistic potential with antibiotics against human pathogens. Gas chromatography-mass spectrometry (GC-MS), Folin- Ciocalteu, 1-diphenyl-2-picrylhydrazyl radical (DPPH), disc diffusion, and minimum inhibitory concentration (MIC) assays were used for identifying phytochemicals, total phenolic content (TPC), antioxidant, and antibacterial activity of ethanolic extract of S.trojana alone and binary combination with selected antibiotics against Gram-positive and Gram-negative bacterial strains, respectively. Furthermore, the combined effects of the extract with classical antibiotics were evaluated by measuring the inhibition zone diameter (IZD). The S.trojana extract showed moderate antibacterial activity with the MIC ranging between 15.625 to 500 µg/mL against human pathogens and the synergistic effect was detected in a dual combination of extract and antibiotics. The extract exhibited high antioxidant activity with a low IC50 value (0.138±0.010 mg/mL). The TPC value was 47.95±0.24 (mg GAE/g extract). After measurements of cytotoxicity were performed, S.trojana can be used alone or combined with antibiotics as an alternative therapy to eliminate pathogens and can be preferred as an antioxidant agent in the pharmaceutical industry.